2016
DOI: 10.1590/1678-775720150437
|View full text |Cite
|
Sign up to set email alerts
|

Solubility and bacterial sealing ability of MTA and root-end filling materials

Abstract: Objective To evaluate solubility and sealing ability of Mineral Trioxide Aggregate (MTA) and root-end filling materials.Material and Methods The materials evaluated were: MTA, Calcium Silicate Cement with zirconium oxide (CSC/ZrO2), and zinc oxide/eugenol (ZOE). Solubility test was performed according to ANSI/ADA. The difference between initial and final mass of the materials was analyzed after immersion in distilled water for 7 and 30 days. Retrograde cavities in human teeth with single straight root canal we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
29
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 27 publications
3
29
0
1
Order By: Relevance
“…A long-term bacterial seal has a decisive influence on the treatment outcome of direct pulp capping [43]. Calcium silicate cements are known to provide an excellent bacterial seal [22,44], whereas calcium hydroxide-based materials might not seal efficiently in long-term because of high solubility and low bonding ability to tooth structure [45]. The advantage of using calcium silicate cements for direct pulp capping instead of calcium hydroxide materials is supported by observations in long-term studies [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…A long-term bacterial seal has a decisive influence on the treatment outcome of direct pulp capping [43]. Calcium silicate cements are known to provide an excellent bacterial seal [22,44], whereas calcium hydroxide-based materials might not seal efficiently in long-term because of high solubility and low bonding ability to tooth structure [45]. The advantage of using calcium silicate cements for direct pulp capping instead of calcium hydroxide materials is supported by observations in long-term studies [14,19].…”
Section: Discussionmentioning
confidence: 99%
“…) which has a good bacterial sealing ability (Espir et al . ). However, this cement has a long setting time and handling difficulty (Roberts et al .…”
Section: Introductionmentioning
confidence: 97%
“…In the present study, the usage of MTA on the pulpal floor was expected to increase success rate in primary molars with furcation lesions since the superior sealing ability of MTA was indicated by many studies and it was also reported that MTA promotes healing in hard tissues [17–20]. MTA was reported to preserve its high pH for a long time owing to calcium release and calcium hydroxide formation [27] and it was reported that MTA shows antimicrobial effect on various microorganisms including E. faecalis and C. albicans [2830].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, another finding in the present study was that, in the successful cases, lesions healed faster in MTA group when compared to IRM group. Faster healing in MTA group can be attributed to the materials sealing ability, high pH, and hard tissue healing stimulation as well as its antimicrobial effect [17–20, 2730]. In addition, canal wall adaptation of this material was reported to be better than Portland cement, IRM, LC GIC, Super EBA, and amalgam [15, 16, 36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation